Mechanical properties of additive manufactured CoCrMo meta-biomaterials for load bearing implants - Siti Rohaida, Mohamed; Saiful Anwar, Che Ghani; Sawangsri, Worapong (Malaysian Tribology Society (MYTRIBOS), 2019)
As compared to human bone properties leads to bone or implant fracture. This study proposes two unique 3-dimensional (3D) meta-biomaterials unit cells which simultaneously attenuate stiffness and stimulate osseointegration. The unit cell of the proposed 3D design is composed of connecting struts making internal structures in the shape of square and diamond. The results under compression suggest all CoCrMo designs exhibit elastic modulus and compression strength that are comparable to the bone. It is demonstrated that the meta-biomaterials can be fabricated using additive manufacturing techniques and their mechanical performance can be tailored by modifying the internal architectures.